Proteção Jurídica Penal, Estado Democrático de Direito e Bens Jurídicos Universais - Pereira, Claudio José (2006)
The legal criminal protecion at the Democratic State of Law was the purpose of study, bound for examine all the legal foundations about brazilian system and procedure penal, in face of new risks introduced by post modern society. Constitucion´s bases of Social and Democratic State of Law make an instrumental whole that supply these new risks´ study according to the actual alternative legal protection, applied. The study of principles which tutelaging all the legal protection system guided the approach about an effective protection of a new way of legal assets. Legal criterians about the individual and metaindividual legal assets, with yours features and function requirements, had been analized under the brazilian State constitutional view. The universal legal assets claim a legal peculiar system, guided by many theorys of justice and truth, lookoing for some eficacy preservetion about human rigths and constitutional guarantees, overcoming the straight limits of individual criminal law. The typification of damaging conducts to the legal order, nowadays, goes trough individual and collective risks. The dissatisfaction about the current criminal law model, organized by tipical constructions, that take advantage of a dangerous model like a formula, demanded critical broaching system, in order to reach an efficient model and fitting to the protection of universal legal assets. The alternative studies and the proposal introductions were the mainly point of this work